Sustained censorship in KZ (2026-03) (Kazakhstan) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Kazakhstan. Data sourced from OONI.
Censorship Incident ID: KZ-2026-0192. Severity: critical. Confidence: 72%